2017
DOI: 10.4047/jap.2017.9.5.387
|View full text |Cite
|
Sign up to set email alerts
|

Effects of staining liquids and finishing methods on translucency of a hybrid ceramic material having two different translucency levels

Abstract: PURPOSEBeverages may affect the translucency of esthetic dental restorative materials. The aim of the present study was to investigate the effects of coffee and red wine on the translucency of a PICN material with two translucency levels, and finished with different methods.MATERIALS AND METHODS2M2 high translucent and translucent VITA Enamic hybrid ceramic blocks were investigated. Rectangular specimens with the dimensions of 12 mm × 14 mm × 2 mm were prepared. The specimens were finished and polished with di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 27 publications
1
13
0
1
Order By: Relevance
“…HT and T groups specimens were divided into 4 groups. Different surface finishing procedures were applied to the specimens using the methods described in a previous study [ 20 , 21 ]: Control group: no surface procedure applied; Technical group: Vita Enamic Technical Kit applied; Clinical group: Vita Enamic Clinical Kit applied; Glaze group: Vita Enamic glaze applied. After completing the surface procedures, the thickness of the each specimen was determined with a caliper (Mitutoyo Corporation, Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…HT and T groups specimens were divided into 4 groups. Different surface finishing procedures were applied to the specimens using the methods described in a previous study [ 20 , 21 ]: Control group: no surface procedure applied; Technical group: Vita Enamic Technical Kit applied; Clinical group: Vita Enamic Clinical Kit applied; Glaze group: Vita Enamic glaze applied. After completing the surface procedures, the thickness of the each specimen was determined with a caliper (Mitutoyo Corporation, Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the optical and surface properties of these materials can change within the oral cavity. Several studies have reported that acidic solutions, including cola, orange juice, red wine, coffee, and gastric acid, can change the optical properties and surface roughness of tooth‐coloured dental restorative materials . In addition, several oral hygiene solutions currently on the market can also affect the colour of dental restoration materials .…”
mentioning
confidence: 99%
“…Increasing the size of filler particles can increase light absorption and cause multi-directional light dispersion within the hybrid composite blocks. The more translucent hybrid blocks showed better color stability than the less translucent hybrid blocks when immersed in red wine [ 16 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the TP was evaluated by measuring the color coefficients on a white and black background. Translucency has been emphasized as one of the primary factors in controlling the esthetic outcome because it makes esthetic restorations appear more natural [ 15 , 16 ]. However, little information is available regarding the translucent characteristics of contemporary CAD/CAM hybrid composite blocks.…”
Section: Introductionmentioning
confidence: 99%